Summary of the Workshop on Ecological Effects of Hydrocarbon Spills in Alaska - Costerton, J.W.; Brunskill, G.J.; Hutchinson, T.; Widden, P. (ARCTIC, 1978)
In any study of the effects of the introduction of an organic compound, such as oil, into a particular environment, such as the Arctic we should, at the outset separate two basic responses: the responses of those organisms (largely bacteria and fungi) to whom the oil is a nutrient to be attacked and eventually decomposed, from the responses of those organisms (largely plants and animals) to whom the oil is a physical and chemical agent of potential toxicity to be tolerated with varying degrees of success. . both groups really function as mixed populations that exhibit dynamic responses to environmental changes, such as oil spills, but our perception of the effects of these changes is largely population-oriented in the decomposers and species-oriented among higher organisms. . The actual removal of oil from the Arctic environment depends on a combination of physical weathering and microbial decomposition . Thus a general principle of microbial ecology is sustained here in that the addition of an organic material to a system stimulates the development of a specific microbial population capable of using that material as a nutrient. The rate of this decomposition process is of maximum importance and it obviously depends on the robustness of the initial microbial population and on nutrient limitation. . One of the special problems of the Arctic is the very slow rate at which these decomposer populations develop significant activities . and accessory nutrient supplementations may be required to achieve acceptable rates of hydrocarbon decomposition. A very important facet of oil degradation is the relative rates at which the different components of oil are broken down by bacteria and fungi. . There are many reasons why oil may be toxic to animals . Oil appears to constitute a fairly general "contact herbicide" whose direct application is most often toxic to plants. . plants vary in their sensitivity to this "contact herbicide" and sensitivity mapping . and bioassays of the sensitivity of specific plants under field ...